PENGARUH CAPITAL ADEQUACY RATIO, BANK SIZE DAN BI RATE TERHADAP RISIKO KREDIT (NPL) PADA PERUSAHAAN PERBANKAN - Sintya Kumala, Putu Ayu; Santi Suryantini, Ni Putu (E-Jurnal Manajemen; Vol 4 No 8 (2015), 2015)
The economic crisis of 2008 have an impact on companies in the country of Indonesia, one of the banking company. The main activities of banking, namely collector and disbursed in the form of loans to customers, from lending activities may pose a risk of non-performing loans (NPL). The research objective was to determine the effect of CAR, bank size and the BI Rate to credit risk simultaneously in the period 2009 - 2013 with a sample of 15 banking companies. Test method using multiple linear regression, where the results of this study indicate CAR significant effect on credit risk (NPL). Bank Size and BI Rate are two variables that effect is not noticeable on Credit Risk (NPL) for banking companies listed in Indonesia Stock Exchange (IDX).
Keywords: Non Performing Loan (NPL), Capital Adequacy Ratio (CAR), Bank Size and Interest Rate BI.